The precursor of secreted aspartic proteinase Sapp1p from Candida parapsilosis can be activated both autocatalytically and by a membrane-bound processing proteinase - Dostál, Jirí; Dlouhá, Helena; Malon, Petr; Pichová, Iva; Hrusková-Heidingsfeldová, Olga (Biological chemistry, 2005)
Opportunistic pathogens of the genus Candida produce secreted aspartic proteinases (Saps) that play an important role in virulence. Saps are synthesized as zymogens, but cell-free culture supernatants of Candida spp. contain only mature Saps. To study the zymogen conversion, the gene encoding a precursor of C. parapsilosis proteinase Sapp1p was cloned, expressed in E. coli and the product was purified. When placed in acidic conditions, the precursor was autocatalytically processed, yielding an active proteinase. The self-activation proceeded through an intermediate product and the resulting enzyme was one amino acid shorter than the authentic enzyme. This truncation did not cause changes in proteinase activity or secondary structure compared to the authentic Sapp1p. Accurate cleavage of the pro-mature junction, however, required a processing proteinase. A crude membrane fraction prepared from C. parapsilosis cells contained an enzyme with Kex2-like activity, which processed the Sapp1p precursor at the expected site. The pro-segment appeared to be indispensable for Sapp1p to attain an appropriate structure. When expressed without the pro-segment, the Sapp1p mature domain was not active and had a lower content of alpha-helical conformation, as measured by circular dichroism. A similar effect was observed when a His(6)-tag was linked to the C-terminus of Sapp1p or its precursor.
Keywords: Protease Inhibitors; substrátová specifita; histidin; Amino Acid Sequence; proteasy; molekulární sekvence - údaje; geny hub; inhibitory proteas; Aspartic Acid Endopeptidases; Molecular Sequence Data; sekvence aminokyselin; buněčná membrána; Histidine; Saccharomyces cerevisiae Proteins; Peptide Hydrolases; Substrate Specificity; proproteinkonvertasy; western blotting; aspartátové endopeptidasy; Cell Membrane; Genes, Fungal; Proprotein Convertases; Blotting, Western; Candida; Enzyme Precursors; prekurzory enzymů; Saccharomyces cerevisiae - proteiny